Critical Discourse Analysis of Cultural Diversity Depicted in Indonesian EFL Secondary School Textbook: English - Diah Paradita Sekar Ningrum; Yousef Bani Ahmad (Prodi Tadris Bahasa Inggris, 2024)
Cultural diversity frequently causes a number of challenging issues. Ethnic conflicts frequently arise in Indonesia as a result of a lack of tolerance and respect for others. Ethnic conflicts occur not only in adults but frequently involve school-age children. Therefore, multicultural education is needed. One of the important tools in learning activity is textbook. Thus, this study aimed to explain the cultural dimension predominantly presented in the textbook entitled Bahasa Inggris Untuk SMA/MA/SMK/MAK Kelas 10. This study implemented a qualitative method and the data were analyzed by using Critical Discourse Analysis. In addition, this study also adopted Huberman, Miles, and Sladana (2014) model of qualitative data analysis which consists of four stages: data collection, data reduction, data presentation, and conclusion drawing. The findings showed there were 60 cultural contents that cover the four dimensions of culture; Products, Practices, Perspectives, and Persons in the textbook. Furthermore, the most dominant cultural dimension found is Products with the frequency of 36, whereas the second most frequently occurring element is Persons which is 21. Perspectives is the third dimension that often occurs with the frequency of 2, followed by Practices with a frequency of 1. This finding suggests further research is needed on teaching methods, strategies, or techniques teachers use in the classroom to teach cultural diversity in the textbook.